If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(8 + -1x) + -3x(5 + -3x) = -26 + -2x(7 + -2x) (8 * 5x + -1x * 5x) + -3x(5 + -3x) = -26 + -2x(7 + -2x) (40x + -5x2) + -3x(5 + -3x) = -26 + -2x(7 + -2x) 40x + -5x2 + (5 * -3x + -3x * -3x) = -26 + -2x(7 + -2x) 40x + -5x2 + (-15x + 9x2) = -26 + -2x(7 + -2x) Reorder the terms: 40x + -15x + -5x2 + 9x2 = -26 + -2x(7 + -2x) Combine like terms: 40x + -15x = 25x 25x + -5x2 + 9x2 = -26 + -2x(7 + -2x) Combine like terms: -5x2 + 9x2 = 4x2 25x + 4x2 = -26 + -2x(7 + -2x) 25x + 4x2 = -26 + (7 * -2x + -2x * -2x) 25x + 4x2 = -26 + (-14x + 4x2) Add '-4x2' to each side of the equation. 25x + 4x2 + -4x2 = -26 + -14x + 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 25x + 0 = -26 + -14x + 4x2 + -4x2 25x = -26 + -14x + 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 25x = -26 + -14x + 0 25x = -26 + -14x Solving 25x = -26 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. 25x + 14x = -26 + -14x + 14x Combine like terms: 25x + 14x = 39x 39x = -26 + -14x + 14x Combine like terms: -14x + 14x = 0 39x = -26 + 0 39x = -26 Divide each side by '39'. x = -0.6666666667 Simplifying x = -0.6666666667
| 3x+6x+4=2x+5x+16 | | 7=10+x | | 17x^2-12=0 | | 15=10+x | | (x-7)(3x+1)=0 | | 0.2y+0.4y-0.3y= | | 125w^3z^9-8s^3=0 | | h=-16t^2+4.5t | | x-7.2=-6.1 | | 0.13y+0.05(y+2000)=1720 | | 0.3y+0.05(y+2000)=1720 | | -12p^2+30p=0 | | 1*(6*6.5-4)=4*6.5-9 | | x+8x+60+3x=180 | | 2x^2+x-x^2+2x-10= | | 5(x+4)=4x+15 | | 56+(98-43)-32+76= | | 67-4x=5x+20 | | x^2+y^2-6x+4y-3=0 | | 12x^2+37x+6=67 | | 12x^2+37x+6=0 | | 12x^2+37x=0 | | 16x^2=0 | | -(4y+4)-(-3y-5)=-2 | | 15x^2+4x+12=0 | | 12(3x-1)=3(12x+7) | | -1w=6w-35 | | 6+18z-3=4z+99-2z | | -[10z-(14z+10)]=10+(3z+7) | | -[10z-(14z+10)]=(3z+7) | | 2x+17x=38 | | -57x-2=-1 |